ChemInform Abstract: Palladium‐Catalyzed Synthesis of 2‐Aminobenzoxazinones by Aerobic Oxidative Coupling of Anthranilic Acids and Isocyanides. Issue 13 (1st April 2014) - Vlaar, Tjoestil; Orru, Romano V. A.; Maes, Bert U. W.; Ruijter, Eelco
Abstract The presented scalable reaction does not work for anthranilic acids bearing NO2, I, OH, or COOH substituents.